Alternative splicing and parallel patterns of gene expression underlie population and life history divergence in an amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikloaj; Brady, Steven (2025)
Keywords: Alternative splicing; Amphibian; Biology; Computational biology; Demography; Divergence (linguistics); Ecology; Evolutionary biology; Gene; Gene expression; Genetics; Life history; Messenger RNA; Population; RNA splicing; Sociology; dept.bio

Alternative Splicing and Gene Expression Variation Underlie Population and Life History Differences in an Amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikolaj; Brady, Steven (Ecology and Evolution, 2025)
ABSTRACT Phenotypic variation is common across life history and among populations occupying different environments, yet the molecular mechanisms underlying these axes of divergence remain poorly understood. Much work has focused on gene expression as a link between genetic variation, environmental variation, and phenotypes, but post‐transcriptional processes such as alternative splicing—which affect how transcripts are assembled rather than how much of a transcript is produced—are increasingly recognized as additional modulators of plasticity and adaptation. Here, we examined gene expression and alternative splicing together in the wood frog ( Rana sylvatica ), an amphibian with a complex life cycle whose populations differ across replicated gradients of road adjacency and associated pollution. We found extensive transcriptomic differences between hatchlings and adults, with thousands of genes differentially expressed or spliced. Individuals clustered strongly by population for both expression and splicing. Differences at the habitat level were less extensive, but revealed two differentially expressed genes ( HSP70 and Gpsm2 ) and one differentially spliced gene ( Cd82 ) that consistently distinguished roadside and woodland populations. Overall, genetic differentiation between populations was low, suggesting that phenotypic and transcriptomic differences likely emerge in the presence of gene flow and reflect plastic responses. Together, these results highlight transcriptomic plasticity as an important mechanism shaping variation across both development and population differentiation.
Keywords: Alternative splicing; Amphibian; Gene; Gene expression; Genetic variation; Phenotypic plasticity; Population; Transcriptome; alternative splicing; dept.bio; gene expression; local adaptation; maladaptation; population divergence

Conservation through the lens of (mal)adaptation: Concepts and meta-analysis - Derry, Alison Margaret; Fraser, Dylan J.; Brady, Steven P.; Astorg, Louis; Lawrence, Elizabeth R.; Martin, Gillian K.; Matte, Jean-Michel; Dastis, Jorge Octavio Negrín; Paccard, Antoine; Barrett, Rowan D. H.; Chapman, Lauren J.; Lane, Jeffrey E.; et al. (Evolutionary Applications, 2019)
Evolutionary approaches are gaining popularity in conservation science, with diverse strategies applied in efforts to support adaptive population outcomes. Yet conservation strategies differ in the type of adaptive outcomes they promote as conservation goals. For instance, strategies based on genetic or demographic rescue implicitly target adaptive population states whereas strategies utilizing transgenerational plasticity or evolutionary rescue implicitly target adaptive processes. These two goals are somewhat polar: adaptive state strategies optimize current population fitness, which should reduce phenotypic and/or genetic variance, reducing adaptability in changing or uncertain environments; adaptive process strategies increase genetic variance, causing maladaptation in the short term, but increase adaptability over the long term. Maladaptation refers to suboptimal population fitness, adaptation refers to optimal population fitness, and (mal)adaptation refers to the continuum of fitness variation from maladaptation to adaptation. Here, we present a conceptual classification for conservation that implicitly considers (mal)adaptation in the short-term and long-term outcomes of conservation strategies. We describe cases of how (mal)adaptation is implicated in traditional conservation strategies, as well as strategies that have potential as a conservation tool but are relatively underutilized. We use a meta-analysis of a small number of available studies to evaluate whether the different conservation strategies employed are better suited toward increasing population fitness across multiple generations. We found weakly increasing adaptation over time for transgenerational plasticity, genetic rescue, and evolutionary rescue. Demographic rescue was generally maladaptive, both immediately after conservation intervention and after several generations. Interspecific hybridization was adaptive only in the F1 generation, but then rapidly leads to maladaptation. Management decisions that are made to support the process of adaptation must adequately account for (mal)adaptation as a potential outcome and even as a tool to bolster adaptive capacity to changing conditions.
Keywords: adaptation; demographic rescue; dept.bio; evolutionary rescue; gene flow; genetic rescue; hybridization; peer-reviewed; transgenerational plasticity; translocation

Causes of maladaptation. - Brady, Steven P; Bolnick, Daniel I; Angert, Amy L; Gonzalez, Andrew; Barrett, Rowan D H; Crispo, Erika; Derry, Alison M; Eckert, Christopher G; Fraser, Dylan J; Fussmann, Gregor F; Guichard, Frederic; Lamy, Thomas; et al. (Evolutionary applications, 2019)
Evolutionary biologists tend to approach the study of the natural world within a framework of adaptation, inspired perhaps by the power of natural selection to produce fitness advantages that drive population persistence and biological diversity. In contrast, evolution has rarely been studied through the lens of adaptation's complement, maladaptation. This contrast is surprising because maladaptation is a prevalent feature of evolution: population trait values are rarely distributed optimally; local populations often have lower fitness than imported ones; populations decline; and local and global extinctions are common. Yet we lack a general framework for understanding maladaptation; for instance in terms of distribution, severity, and dynamics. Similar uncertainties apply to the causes of maladaptation. We suggest that incorporating maladaptation-based perspectives into evolutionary biology would facilitate better understanding of the natural world. Approaches within a maladaptation framework might be especially profitable in applied evolution contexts - where reductions in fitness are common. Toward advancing a more balanced study of evolution, here we present a conceptual framework describing causes of maladaptation. As the introductory article for a Special Feature on maladaptation, we also summarize the studies in this Issue, highlighting the causes of maladaptation in each study. We hope that our framework and the papers in this Special Issue will help catalyze the study of maladaptation in applied evolution, supporting greater understanding of evolutionary dynamics in our rapidly changing world.
Keywords: adaptation; dept.bio; fitness; global change; maladaptation; peer-reviewed

Understanding maladaptation by uniting ecological and evolutionary perspectives - Brady, Steven P.; Bolnick, Daniel I.; Barrett, Rowan D. H.; Chapman, Lauren; Crispo, Erika; Derry, Alison M.; Eckert, Christopher G.; Fraser, Dylan J.; Fussmann, Gregor F.; Gonzalez, Andrew; Guichard, Frederic; Lamy, Thomas; et al. (The American Naturalist, 2019)
Evolutionary biologists have long trained their sights on adaptation, focusing on the power of natural selection to produce relative fitness advantages while often ignoring changes in absolute fitness. Ecologists generally have taken a different tack, focusing on changes in abundance and ranges that reflect absolute fitness while often ignoring relative fitness. Uniting these perspectives, we articulate various causes of relative and absolute maladaptation and review numerous examples of their occurrence. This review indicates that maladaptation is reasonably common from both perspectives, yet often in contrasting ways. That is, maladaptation can appear strong from a relative fitness perspective, yet populations can be growing in abundance. Conversely, resident individuals can appear locally adapted (relative to nonresident individuals) yet be declining in abundance. Understanding and interpreting these disconnects between relative and absolute maladaptation, as well as the cases of agreement, is increasingly critical in the face of accelerating human-mediated environmental change. We therefore present a framework for studying maladaptation, focusing in particular on the relationship between absolute and relative fitness, thereby drawing together evolutionary and ecological perspectives. The unification of these ecological and evolutionary perspectives has the potential to bring together previously disjunct research areas while addressing key conceptual issues and specific practical problems. © 2019 by The University of Chicago. All rights reserved.
Keywords: Adaptation; Fitness; Global change; Maladaptation; adult; article; dept.bio; drawing; ecologist; environmental change; female; global change; human; human experiment; male; natural selection; peer-reviewed; resident